Genotoxicity assessment of amino zinc nanoparticles in wheat (Triticum aestivum L.) as cytogenetical perspective - Abdelsalam, Nader R.; Abdel-Megeed, Ahmed; Ghareeb, Rehab Y.; Ali, Hayssam M.; Salem, Mohamed Z.M.; Akrami, Mohammad; Al-Hayalif, Muwafaq F.A.; Desoky, El-Sayed M. (Saudi journal of biological sciences, 2022)
•Using and impact of nanoparticles in agriculture.•Genotoxicity of nanoparticles in plant.•Effect of commercial amino zinc nanoparticles on cell division.•The harmful effect of commercial amino zinc nanoparticles in chromosomal structure. Nanoparticles have a positive impact in several subjects especially in agriculture, while their safety is still being debated. Numerous commercial nano pesticide, insecticides, and fertilizers products are found in the local markets without any intensely studies on the side effect of these products on plant, human as well as environmental effects. The present study aimed to evaluate the genotoxicity of commercial amino zinc nanoparticles (AZ NPs) on Triticum aestivum L. during seeds germination and root elongation using concentration ranges (50, 100, and 150 ppm) at different exposure times (8, 16 and 24 hrs). Long term exposure to AZ NPs, exhibited only slight variation in germination rates and the elongation of roots was affected by AZ NPs treatment ranged from 97.66 to 100%. Significant reduction in the mitotic index was 35.33% after 24 hrs and 150 ppm of AZ NPs, was also observed comparing with control which was 88.0%. Genotoxicity was evaluated at a cytological level in root meristems that revealed sever variations in mitotic activity, chromosomal aberrations, and micronuclei release. Results exhibited that nano amino zinc could enter effortlessly into the cells and inhibit the normal cellular function. The decrease in the emergence of chromosomal aberrations resulting from AZ NPs exposure in a dose-dependent manner was clearly indicated that AZ NPs has induced genotoxic effect on wheat root tips.